Response of vitamin B-6 deficiency and the carpal tunnel syndrome to pyridoxine. - Ellis, J M (1982)
The specific activities and percentage deficiencies of the glutamic oxaloacetic transaminase of erythrocytes (EGOT) were determined for patients with carpal tunnel syndrome (CTS) diagnosed by clinical examination and electrical conduction data; the EGOT data revealed a severe deficiency of vitamin B-6. After double-blind treatment with pyridoxine and placebo, two physicians identified those receiving pyridoxine (clinically improved) and those receiving placebo (did not improve) without error, P less than 0.0078. Correcting a deficiency of the coenzyme at receptors of existing molecules of the apoenzyme appears to take place within days; correction of the deficiency in the number of molecules of the transaminase takes place over 10-12 weeks. The clinical response, appraised by the diminution of the symptoms of CTS, was correlated only with the restored levels of the transaminase which presumably results from a translational long-term increase in the number of molecules of EGOT by a mechanism activated by correcting a deficiency of pyridoxal 5'-phosphate. Apparent Km values of EGOT were identical for groups of patients with CTS and others without CTS but with identical specific activities, indicating that CTS is a primary deficiency of vitamin B-6 rather than one of a dependency state. Clinical improvement of the syndrome with pyridoxine therapy may frequently obviate hand surgery.